Organização das Mulheres Indígenas de Roraima (OMIR) : uma análise das demandas e reivindicações das mulheres indígenas na luta por direitos - Moura, Luana Almeida de (2019)
This research aims to discuss the process of constructing the demands and claims of indigenous women of the Organization of Indigenous Women of Roraima (OMIR). Therefore, it presents the historical context of OMIR, as a backdrop to understand the changes that have occurred over the years of the organization's performance. In addition, it analyzes categories of analysis as indigenous movement, gender and agency in the indigenous context, in order to understand the process of constructing the demands of indigenous women. Then, documents such as reports of assemblies, letters, newspapers, books, articles, dissertations, theses and, mainly, interviews made with women leaders and participants of OMIR were essential for conducting the research. The demands and claims of indigenous women have been improved over the years. Initially, it was due to the claim of participation in decisions, in the fight for the defense of the land, for the defense of a differentiated education and health, for the combating alcoholic beverages in their communities, more general demands. Over the years new demands were inserted, among them, the search for spaces to discuss their specificities, the fight against female violence, discuss about women's health, self-sustainability projects for the economic development of Community (Project of poultry farming, fish farming, cattle breeding, etc.), that is, there were changes in demands in the different contexts experienced.